On the randomized multiple row-action methods for solving linear least-squares problems - Zuo, Qian; Wu, Nian-Ci; Liu, Chengzhi; Wang, Yatian (Numerical algorithms, 2025)
The randomized row-action method is a popular representative of the iterative algorithm because of its efficiency in solving the overdetermined and consistent systems of linear equations. In this paper, we present an extended randomized multiple row-action method to solve a given overdetermined and inconsistent linear system and analyze its computational complexities at each iteration. We prove that the proposed method can linearly converge in the mean square to the least-squares solution with a minimum Euclidean norm. Several numerical studies are presented to corroborate our theoretical findings. The real-world applications, such as image reconstruction and large noisy data fitting in computer-aided geometric design, are also presented for illustration purposes.